Approach to Development Judo Training Boxing and Fighting for Safety Management of Police Cadets Case Study: RPCA - Meetavon, Sunti; Jaksudechovanith, Naruedolrapassorn (Ph.D. in Social Sciences Journal, 2021)
This article research objectives which are (1) To study the Approach to Development Judo Training Boxing and Fighting for Safety Management of Police Cadets Case study: RPCA. (2) To study problems and obstacles Approach to Development Judo Training Boxing and Fighting for Safety Management of Police Cadets Casestudy: RPCA. (3) To Achieve Approach to Development Judo Training Boxing and Fighting for Safety Management of Police Cadets Casestudy: RPCA to be Appropriate. This study uses Mixed Methods Research. The quantitative research was conducted by sampling 233 respondents and analyzed the data. Qualitative Research by Focus Group to survey opinions and in-depth interview for the development of safety management in Judo, Boxing and Combat Training. The result of this case study shows that Safety Management in Judo Boxing and Fighting. There are still problems. Safety in the study of cadets in martial arts, boxing and martial arts. Danger in learning difficult postures. Dangerous Lesson time Teachers are not enough. Police officers lacked motivation to study, so they improved their study time by adding more classes. Adding teachers to lecturers Improvement of equipment used in teaching and learning. Learning martial arts, boxing and martial arts requires a grade. And do not underestimate during the course. Teachers and students need first aid knowledge. Knowledge of sports science. Should build a sports science center in the police academy. To be the center Sports Science By the principles.